Review on liquid film flow and heat transfer characteristics outside horizontal tube falling film evaporator: Cfd numerical simulation - Wang, Qifan; Li, Minxia; Xu, Wenjie; Yao, Liang; Liu, Xuetao; Su, Dandan; Wang, Pai (International journal of heat and mass transfer, 2020)
•CFD numerical calculation method of horizontal-tube falling film evaporation is summarized.•Microscopic mechanisms of thermodynamic, flow and structural parameters on liquid film flow characteristics and heat transfer are analyzed by summarized CFD simulation results.•Improvement and research directions of CFD simulation are suggested. The horizontal-tube falling film evaporation is an efficient heat transfer technology for energy-saving, with good economic and environmental benefits. In the falling film evaporation technology, the thickness and uniformity of liquid film are considered as important hydrodynamic characteristics that influence the heat transfer of fluid greatly. However, through experimental methods, it is difficult to obtain the microscopic characteristics and subtle changes of the velocity and temperature distribution inside the liquid film, and hard to describe the gas-liquid interface during the evaporation process of the liquid on the tube surface. Therefore, CFD simulation is used in the researches on the falling film flow and heat transfer characteristics outside the horizontal tube. This paper mainly reviewed the CFD simulation work of falling film evaporation outside the horizontal tube in the existing literatures. The models used by researchers were made a summary. The effects and microscopic mechanisms of flow parameters such as spray density, thermodynamic parameters such as the surface tension of liquid, structural parameters such as the liquid distributor and evaporation characteristics of heat transfer tubes and tube bundle were summarized and analyzed. Based on the researches’ CFD simulation results of hydrodynamics and heat and mass transfer of falling film evaporation, it is found that these parameters have their own reasonable ranges to ensure the efficient operation of falling film evaporators under specific operation conditions. Beyond the reasonable range, the formation of liquid film on the tube surface is to be destroyed, it will result in the decrease of heat transfer performance and the dryout. In addition, by adjusting the magnitude of the surface tension, wall adhesion, inertia force and other forces, the change of these parameters leads to the generation of vortex and recirculation phenomenon, the decrease of liquid film thickness and the enhancement of liquid film fluctuation, so as to reduce the thermal boundary layer thickness and enhance the heat and mass transfer performance of the film evaporation process. It is considered that under the comprehensive action of multi-parameters, the three-dimensional distribution of flow characteristics and heat transfer coefficient of multicomponent working fluid, as well as the change of flow pattern between tube bundles, are the improvement directions of current CFD simulation. And the research directions of future CFD simulation are the microscopic hydrodynamic and heat transfer characteristics caused by wall structure reconstruction and the influence of auxiliary components on the falling film evaporation process.